Composer Complete Critical Editions in the Twenty-First Century: A Case Study of Béla Bartók. Issue 1 (2019) - Gillies, Malcolm
Abstract : Composer complete critical editions originated in the mid nineteenth-century and remain an important contribution to twenty-first-century scholarship and performance practice. This discussion article, commissioned by the Royal Musical Association Research Chronicle, uses the Béla Bartók Complete Critical Edition, inaugurated in 2016, as the basis of reconsideration of the musicological, performance-related, publishing and business aspects of today's complete editions of composers' works. Gillies looks at the characteristics of the first two Bartók edition volumes, For Children and Concerto for Orchestra, particularly their approach to the composer's use of notation, the representation of their geneses, and some interesting issues about variants, versions, alternatives, replacements, arrangements and deletions. He also considers what a dozen Henle Urtexts, issued on the basis of this complete critical edition's research, seek to present for performers, particularly in their use of Bartók's own recordings as exemplars as well as the presentation in his folk-music treatises of melodies on which these pieces are based. Gillies's consideration also reveals some of the bases of the Bartók complete edition in the post-war 'Neue Ausgabe' critical series, with some later influence from Schoenberg and Debussy editions. After looking at changes in format and related products, including thematic catalogues, and the business models that underpin many complete critical editions, Gillies evaluates the risks that may face the Bartók edition in the future, and suggests how they might best be mitigated.